2015
DOI: 10.1016/j.physbeh.2015.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular activity and chronic pain severity

Abstract: This biobehavioral protocol enables measurement of chronic pain suffering and protection in three dimensions: physical, emotional, and cognitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 91 publications
4
29
0
Order By: Relevance
“…However, the findings also predict that incorrect predominant management of somatic or affective complaints in patients with mainly an affective or somatic mechanism of chronic pain, respectively, will not improve effectiveness of the intervention. Thus, these results are in accord with previous considerations that impacts of affective and somatic components of chronic pain on the patient's condition should be correctly distinguished for their effective management …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, the findings also predict that incorrect predominant management of somatic or affective complaints in patients with mainly an affective or somatic mechanism of chronic pain, respectively, will not improve effectiveness of the intervention. Thus, these results are in accord with previous considerations that impacts of affective and somatic components of chronic pain on the patient's condition should be correctly distinguished for their effective management …”
Section: Discussionsupporting
confidence: 89%
“…In IBS and other chronic pain conditions, multiple autonomic mechanisms have shown associations with components (nociceptive, affective, and cognitive) of the chronic pain experience . For example, increases in diastolic blood pressure (DBP) and decreases in HRV have been associated with decreased BRS, but clinically to either lower nociceptive or higher affective complaints related to pain, respectively .…”
Section: Introductionmentioning
confidence: 99%
“…A finding of higher systolic blood pressure level in this sample of IBS patients is consistent with other studies that found that a systolic blood pressure increase in response to rectal pain stimulation was greater and prolonged in patients with IBS compared to healthy controls and that chronic pain is a significant predictor of increased blood pressure beyond the effects of traditional demographic risk [18,19,37]. Sustained increase of blood pressure level is considered to be an indicator of a pain regulation (‘pain killer’) mechanism [3840]. In the present study, this pain alleviating mechanism associated with a diastolic blood pressure increase was affirmed and supported a recent finding of the impact of baroreflex function on endogenous control of acute pain coupled mainly with a diastolic blood pressure increase [41].…”
Section: Discussionsupporting
confidence: 83%
“…From an evolutionary viewpoint, this adaptation ‘blood pressure’ mechanism may help alleviate a recovery of physical functioning after impairments. Difference in effect size with respect to blood pressure measures obtained in office and laboratory may be explained by either the moderation effect of arousal variations between different settings [23,40,49,50] or worse accuracy of non-invasive beat-to-beat monitors in measuring absolute levels of blood pressure [51]. …”
Section: Discussionmentioning
confidence: 99%
“…Activity of the autonomic nervous system is altered in chronic pain disorders in general including chronic visceral pain disorders such as irritable bowel syndrome (IBS) . In most previous studies, these alterations have been investigated using traditional indicators of CV system regulation such as baroreflex sensitivity (BRS), heart rate variability (HRV), and BP .…”
Section: Introductionmentioning
confidence: 99%